1992
DOI: 10.1152/ajpheart.1992.263.6.h1946
|View full text |Cite
|
Sign up to set email alerts
|

New nonradioactive microspheres and more sensitive X-ray fluorescence to measure regional blood flow

Abstract: We developed new nonradioactive microspheres and used more sensitive X-ray fluorescence spectrometers than used previously to measure regional blood flow in the heart and other organs. We demonstrated the chemical stability of eight kinds of heavy element-loaded microspheres and validated their use for regional blood flow measurement by comparing duplicate flows measured with radioactive and/or nonradioactive microspheres in both acute and chronic dog experiments. The wavelength-dispersive spectrometer (Philip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…A number of non-radioactive alternatives have been proposed, including coloured microspheres (Hale et al 1988;Kowallik et al 1991;Hakkinen et al 1995;Degens et al 1996) and X-ray fluorescent microspheres (Morita et al 1990;Mori et al 1992), although they have been shown to have some disadvantages. For example, coloured microspheres may underestimate RBF, since they have limited resolution due to significant spectral overlap among different colours, while data variance is high as a result of the low signal intensity (Hale et al 1988;Kowallik et al 1991;Prinzen & Glenny, 1994;Degens et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A number of non-radioactive alternatives have been proposed, including coloured microspheres (Hale et al 1988;Kowallik et al 1991;Hakkinen et al 1995;Degens et al 1996) and X-ray fluorescent microspheres (Morita et al 1990;Mori et al 1992), although they have been shown to have some disadvantages. For example, coloured microspheres may underestimate RBF, since they have limited resolution due to significant spectral overlap among different colours, while data variance is high as a result of the low signal intensity (Hale et al 1988;Kowallik et al 1991;Prinzen & Glenny, 1994;Degens et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm infarct size reduction by edaravone in relation to the effect of collateral flow, regional MBF was assessed by non-radioactive microspheres (Sekisui Plastic Co., Ltd., Tokyo), as previously described (17). Briefly, 1 ml of the microsphere suspension (2 to 4 × 10 6 spheres) was injected into the left atrium 85 min after the onset of coronary occlusion.…”
Section: Regional Blood Flow and Infarct Sizementioning
confidence: 99%
“…17 Nonradioactive microspheres (Sekisui Plastic Co) made of inert plastic were labeled with bromine. Microspheres were administered at 80 minutes after the start of coronary occlusion.…”
Section: Measurement Of Infarct Size and Collateral Blood Flowmentioning
confidence: 99%